The effect of fruit maturation stage on seed germination of iaa9-3 and iaa9-5 tomato mutants - Al Aufa, Elfa Muhammad Ihsan; Mubarok, Syariful; Nuraini, Anne; Budiarto, Rahmat; Waluyo, Nurmalita; Ezura, Hiroshi (Kultivasi, 2024)
One of the internal factors that play an important role in seed quality is the level of the phytohormone auxin. Efforts to increase auxin in seeds include developing new varieties with increased indigenous auxin, such as those found in mutant tomatoes from Micro-Tom, namely iaa9-3 and iaa9-5. This research was conducted to determine the germination response of iaa9-3 and iaa9-5 mutant tomato seeds at different levels of the fruit maturation stage. The research was carried out at the Seed Technology Laboratory, Faculty of Agriculture, Padjadjaran University, and the Seed Testing Laboratory of the Center for Standard Testing of Vegetable Plant Instruments. The response design used was a completely randomized factorial design consisting of two factors and repeated three times. The first factor was the iaa9-3, iaa9-5, and Wild-Type Micro-Tom (WT-MT) mutants as controls. The second factor is the fruit maturation stage, which consists of Breaker, Pink, and Red. The research results showed that there was an interaction between genotype and fruit maturation stage on the parameters of germination, growth simultaneity, and hypocotyl length.  The harvest stage for tomatoes to produce normal strong seed germination was the pink stage in all tomato genotypes tested. The best germination rate was shown by WTMT seeds at the pink stage, genotype iaa9-3 at the red stage, and genotype iaa9-5 at the red or pink stage. The effect of fruit maturity stage on the synchronization of sprout growth was relatively not significantly different in mutant tomatoes, but it had an effect in WTMT tomatoes, namely the best pink stage.